Impacts of hyperthermic chemotherapeutic agent on cytotoxicity, chemoresistance-related proteins and PD-L1 expression in human gastric cancer cells - Bor-Chyuan Su; Guan-Yu Chen; Chun-Ming Yang; Wei-Ting Chuang; Meng-Chieh Lin; Pei-Ling Hsu; Chu-Wan Lee; Chih-Cheng Cheng; Shih-Ying Wu; Bo-Syong Pan; Hsin-Hsien Yu (International Journal of Hyperthermia)
Objective: Gastric cancer with peritoneal metastasis is considered to be final stage gastric cancer. One current treatment approach for this condition is combined cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (HIPEC). However, the therapeutic mechanisms of HIPEC remain largely undescribed. Method: In order to assess the cellular effects of HIPEC in vitro, we treated AGS human gastric adenocarcinoma cells with or without 5-fluorouracil (5-Fu) at 37 °C or at 43 °C (hyperthermic temperature) for 1 h followed by incubation at 37 °C for 23 h. The impacts of hyperthermia/5-Fu on apoptosis, cell survival signals, oxidative stress, chemoresistance-related proteins and programmed death-ligand 1 (PD-L1) expression were measured. Results: Our results showed that hyperthermia potentiates 5-Fu-mediated cytotoxicity in AGS cells. Furthermore, the combination of 5-Fu and hyperthermia reduces levels of both phosphorylated STAT3 and STAT3, while increasing the levels of phosphorylated Akt and ERK. In addition, 5-Fu/hyperthermia enhances reactive oxygen species and suppresses superoxide dismutase 1. Chemoresistance-related proteins, such as multidrug resistance 1 and thymidylate synthase, are also suppressed by 5-Fu/hyperthermia. Interestingly, hyperthermia enhances 5-Fu-mediated induction of glycosylated PD-L1, but 5-Fu-mediated upregulation of PD-L1 surface expression is prevented by hyperthermia. Conclusion: Taken together, our findings provide insights that may aid in the development of novel therapeutic strategies and enhanced therapeutic efficacy of HIPEC.